THE DYNAMICS STUDY OF OFFSHORE DRILL SYSTEM (OVERVIEW) - Слабий, Орест Олегович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The review of existing designs drilling systems used in the drilling of a deep sea. We consider the physical and mathematical models used in the study of the dynamics of the elements of offshore drilling. The analysis of existing methods for studying the dynamics of drilling riser, riser tensioner and drill string heave compensator.